OPTIMALISASI PENGABDIAN MASYARAKAT PADA SEKOLAH PAUD BINAAN - I Made Ardika Yasa (Universitas Muhammadiyah Mataram, 2021)
ABSTRAKPenulisan hasil Pengabdian masyarakat ini bertujuan untuk menggambarkan peningkatan optimalisasi pengabdian masyarakat pada Sekolah PAUD Binaan STAHN Gde Pudja Mataram sehinggaproses pembelajaran di lembaga Pendidikan Anak Usia Dini yang saat ini tidak hanya terbatas teori pada pertemuan atau tatap muka di kelas saja, tapi terus berkembang dengan prangkat dan metode pembelajaran yang menggunakan media peraga. Proses pelaksanaan kegiatan dilakukan dengan mengadakan perencanaan, pelaksanaan dan evaluasi. Adapun dari pelaksanaan kegiatan pengabdian ini merupakan wujud aplikasi dalam melaksanakan salah satu Tri Dharma Perguruan Tinggi pada aspek Pengabdian Masyarakat, sasaran dari kegiatan ini ialah Sekolah PAUD binaan Program Studi PG-PAUD jurusan Dharma Acarya Sekolah Tinggi agama Hindu Negeri Gde Pudja Mataram dimana seperti yang telah kita ketahui bahwa Sekolah PAUD atau Taman Kanak-kanak merupakan salah satu bentuk lembaga pendidikan anak usia dini yang dalam proses pembelajarannya menekankan pada prinsip bermain sambil belajar dan belajar seraya bermain. Optimalisasi pembinaan juga bertujuan untuk mengembangkan pendidikan karakter khususnya yang berlandaskan ajaran agama Hindu sejak dini bagi anak-anak. Oleh karenanya kegiatan pengabdian ini begitu penting, sehingga melalui penulisan laporan ini dapat memberikan gambaran manfaat kegiatan yang dilakukan dan memberikan penguatan wawasan mengenai pentingnya pendidikan dan optimalisasi binaan terhadap pendidikan anak usia dini khususnya dalam pengembangan karakter. Kata kunci: optimalisasi; pengabdian masyarakat; paud binaan. ABSTRACTThis community service aims to improve the optimization of community service at the STAHN Gde Pudja Mataram PAUD School, so that the learning process in Early Childhood Education, which is currently not limited to theory only at meetings or face-to-face class meetings. , but continues to develop with learning methods and tools that use visual media. As for this service activity as a form of application in implementing one of the Tri Dharma Perguruan Tinggi in the aspect of Community Service, the target of this activity is the PAUD Schools assisted by the PG-PAUD Study Program majoring in Dharma Acarya, the State College of Hindu Religion Gde Pudja Mataram where as already we know that PAUD School or Kindergarten is a form of early childhood education institution which in the learning process emphasizes the principle of playing while learning and learning while playing The writing of the results of community service aims to describe the improvement of optimization of community service at the PAUD School Assisted by STAHN Gde Pudja Mataram so that the learning process in early childhood education institutions that are currently not only limited to meetings or face-to-face in the classroom but continues to develop with a prank at and learning methods that use media props. The process of carrying out activities is carried out by conducting planning, implementation and evaluation. As for the performance of this holy activity is a form of application in carrying out one of the Tri Dharma Of Higher Education in the aspect of Community Service, the target of this activity is paud school assisted by PG-PAUD Study Program majoring in Dharma Acarya State Hindu High School Gde Pudja Mataram. In contrast, we already know that PAUD School or Kindergarten is one form of an early childhood education institution that in the learning process emphasizes the principle of playing while learning and learning while playing. Optimization of coaching also aims to develop character education, primarily based on Hindu teachings early on for children. Therefore, this holy activity is so essential that the writing of this report can provide an overview of the benefits of activities carried out and provide reinforcement of insights on the importance of education and optimization of the development of early childhood education, especially in character development. Keywords: optimization; community dedication; paud assisted.